A stereo configuration-activity study of 3-iodo-4-(2-methylcyclohexyloxy)-6-phenethylpyridin-2(2H)-ones as potency inhibitors of HIV-1 variants. Issue 4 (16th December 2015) - Wu, Shaotong; Yin, Qianqian; Zhao, Liang; Fan, Ningning; Tang, Xiaowan; Zhao, Jianxiong; Sheng, Tao; Guo, Ying; Tian, Chao; Zhang, Zhili; Xu, Weisi; Liu, Zhenming; et al.
Abstract : The trans -( S, S )-enantiomer2e turned out to be significantly more potent than its enantiomer2d against wild-type and mutant strains with high selectivity indexes. Abstract : 3-Iodo-4-(2′-methylcyclohexyloxy)-6-phenethylpyridin-2(1 H )-ones, as effective non-nucleoside reverse transcriptase inhibitors, were synthesized and resolved with different configurations. Biological results revealed that the trans -racemate2b exhibited more potent activity than the cis -isomers. Noticeably, the trans -( S, S )-enantiomer2e turned out to be significantly more potent than its counterpart enantiomer2d against wild-type and double-mutant strains with high selectivity indexes.